Medication errors in infants at home - Ojha, Shalini; Choonara, Imti (BMJ, 2017)
The study by Solanki and colleagues involved interviewing 166 parents/grandparents at home regarding the medications that had been prescribed at discharge to their infants, by the hospital staff [1]. As part of the study, the parents were also asked to demonstrate how much medicine they would give. With this methodology, Solanki et al. estimated that two out of three of the infants in their study would have experienced medication errors at home. This is an alarmingly high proportion of medication errors. Fortunately, none of the infants experienced significant harm. The authors have suggested that this high rate may be due to lack of parental education and inadequate pre-discharge counselling. The study was performed in Pondicherry in India. It would be wrong, however, to dismiss the relevance of their findings when considering the possibility of medication errors among neonates discharged from centres from high income countries, such as the U.K.